Aplikasi Chatbot Berbasis Web Menggunakan Metode Dialogflow - Dicki Wahyudi Harahap; liza fitria (E-Jurnal Universitas Samudra, 2020)
Chatbot is a computer program designed to simulate an interactive conversation or communication to the user (human) either through text, voice or visual. Chatbots have been widely used for practical purposes such as online help, personal services, or information acquisition. Along with the rapid development, a quick response is needed, including in the HelpDesk work of the Binjai Pratama Tax Office. In this research, chatbot technology is designed using dialogflow which consists of agent, intent and training phrase. The test results via messenger show that the chatbot system that has been designed can work well and respond according to the keywords or input contained in the training phrase and the appropriate response.